Land Pollution and Environmental Preservation Efforts in Elementary School Education - Chingngaihmuan Ngaihte; Maretha Dellarosa; Ganes Gunansyah (Didaktika: Jurnal Kependidikan, 2026)
Land pollution is a growing environmental concern that impacts soil quality, biodiversity, and human health on a global and local scale. This study investigated the efficacy of a structured environmental education intervention in increasing Grade 5 students' understanding of land contamination and environmental awareness. The intervention was carried out in an elementary school in Surabaya and included video-based instruction, guided discussions, worksheet tasks, collaborative poster making, and written comments. Data were collected and analysed descriptively using worksheet scores, poster assessments, classroom observations, and student reflections. The findings revealed that most students had a strong to exceptional understanding of essential concepts relevant to land contamination, such as its sources, impacts, and prevention measures. Based on worksheet results, twelve out of fourteen students demonstrated good or excellent mastery, whereas poster activities revealed consistent group competence in communicating environmental ideas. Students excelled in organised tasks like true-false and fill-in-the-blank questions, whereas open-ended responses revealed variable levels of written expression. Reflection data revealed improved knowledge and personal responsibility for environmental cleaning. These findings indicate that even a brief, classroom-based intervention can effectively improve primary school pupils' cognitive comprehension and environmental attitudes, emphasising the importance of environmental education in fostering sustainable conduct from an early age.